Dialogue between Muslims and Non-Muslims: Rooting Legitimate in the Light of the Quran and Sunnah(الحوار بين المسلمين وغير المسلمين: تأصيل شرعي في ضوء القرآن والسنة) - Jawwad, Nasser Abdullah Odeh Abdal (Al-Bayān, 2017)
This research aims to enhance the dialogue among Muslims and non-Muslims based on the Quran and the prophet’s traditions. It paves the way by discussing the issue of coexistence between the two communities. This article has the objective to consolidate the principles of two kinds of dialogue: ideological dialogue and realistic dialogue. Next is the discussion of the possibility of Islamic law (Sharia) to coexist with contemporary international law regarding the issue of the right of expression as a human right. Furthermore, this article studies the major ethical methods of dialogue and provides some practical models and examples of dialogue between Muslims and non-Muslims from Islamic history.